Cerebral Blood Flow Velocity and Stress as Predictors of Decision Making. (September 2014) - Reinerman-Jones, Lauren; Parchment, Avonie; Matthews, Gerald; Barber, Daniel; Lackey, Stephanie; Teo, Grace
Predicting decision making may be essential for personnel selection. The present study aimed to predict sustained decision making using measures of subjective state and physiological response to a short task battery. Volunteers completed a short battery of decision tasks, followed by a dynamic task simulating business decision making. Subjective stress state and cerebral blood flow velocity (CBFV) responses to each task suggested that sustained decision making may induce stress and fatigue. Some positive associations were found between CBFV responses to the short battery and long task performance. The right hemisphere CBFV responses taken during the long task correlated highly with long task performance. These findings suggest that hemodynamic response to a verbal task, like the short battery, may provide an effective means for predicting subsequent decision making effectiveness. The findings also suggest that CBFV may access multiple resources required for sustained decision making, localized in left and right hemispheres.